2015
DOI: 10.1115/1.4030377
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Technique for Production of Metal Matrix Composites Reinforced With Carbon Nanotubes

Abstract: The metal matrix composites (MMCs) have been widely used where high specific properties and temperature resistance are required, particularly in aerospace applications. In this work, an ASTM-1100 aluminum alloy in the form of sheets was reinforced with multiwalled carbon nanotubes (MWCNTs) by a novel technique which we have called sandwich technique. Carbon nanotubes (CNTs) are dispersed in a polyvinyl alcohol (PVA) solution; this solution is poured into a container and dried to obtain a reinforced polymer, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In the case of the composite with 2 wt.% of MWCNTs (Figure 6(b)), the alignment was not so good. As explained elsewhere, 29 this poor alignment is probably a result of the low deformability of the reinforced PVA layer during the stretching process, which in turn is due to the high content of MWCNTs.…”
Section: Microstructural Analysis Of Al/mwcntsmentioning
confidence: 85%
See 2 more Smart Citations
“…In the case of the composite with 2 wt.% of MWCNTs (Figure 6(b)), the alignment was not so good. As explained elsewhere, 29 this poor alignment is probably a result of the low deformability of the reinforced PVA layer during the stretching process, which in turn is due to the high content of MWCNTs.…”
Section: Microstructural Analysis Of Al/mwcntsmentioning
confidence: 85%
“…In the evaluated zones, the presence of any aluminum carbide phase was not detected, which confirms the findings of micro X-ray diffraction previously reported. 29 However, several studies have shown the formation of aluminum carbides in this kind of composite materials. In addition, the mechanisms of phase growth when the composites are manufactured at temperatures above their melting point have also been studied.…”
Section: Interfacial Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The need to find high-strength lightweight materials in transportation industries has driven the development of new materials and manufacturing methods to reduce CO2 emissions into the atmosphere.Recently, a new manufacturing process for the production of metal matrix composites reinforced with carbon nanotubes, known as sandwich technique, has been proposed [5][6][7]. This technique produces materials comprised of a metallic matrix and banded structured-layers of multiwalled carbon nanotubes (MWCNTs).…”
mentioning
confidence: 99%
“…Recently, a new manufacturing process for the production of metal matrix composites reinforced with carbon nanotubes, known as sandwich technique, has been proposed [5][6][7]. This technique produces materials comprised of a metallic matrix and banded structured-layers of multiwalled carbon nanotubes (MWCNTs).…”
mentioning
confidence: 99%